Our book of awesome : a celebration of the small joys that bring us together - Pasricha, Neil (Simon & Schuster Canada, 2022)
"From the bestselling author of The Book of Awesome, a new compilation of awesome things and small joys in our lives that bring us together. Award-winning writer Neil Pasricha brings back his trademark laugh-out-loud observations of the world and encourages us to be positive and find gratitude in the simple, free, odd, and silly."--